2002
DOI: 10.1161/hs0202.102730
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Restoration and Reperfusion Injury After Ultraviolet Laser–Facilitated Middle Cerebral Artery Recanalization in Rat Thrombotic Stroke

Abstract: Background and Purpose-A reversible model of focal thrombotic stroke was developed in the rat and examined for histological evidence of reperfusion injury after clinically relevant times of recanalization. Methods-The distal middle cerebral artery of 28 male Sprague-Dawley rats was occluded by 562-nm laser-driven photothrombosis for 0.5, 2, and 3 hours or permanently (each nϭ7) and was recanalized by 355-nm UV laser irradiation. Occlusive material was examined by transmission electron microscopy. Cortical cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…30 This is understandable since leukocyte infiltration occurs much earlier after transient than permanent MCAO, and reperfusion predisposes the brain to an early inflammatory response. Reperfusion does not occur spontaneously in the majority of stroke patients, but recent studies showed promising results with thrombolytic protocols using prourokinase, 14 recombinant tPA, 15 UV laser, 16 and ultrasound. 17 Furthermore, postischemic hyperperfusion occurs in approximately 50% of patients by day 7 after intra-arterial thrombolysis-mediated recanalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 This is understandable since leukocyte infiltration occurs much earlier after transient than permanent MCAO, and reperfusion predisposes the brain to an early inflammatory response. Reperfusion does not occur spontaneously in the majority of stroke patients, but recent studies showed promising results with thrombolytic protocols using prourokinase, 14 recombinant tPA, 15 UV laser, 16 and ultrasound. 17 Furthermore, postischemic hyperperfusion occurs in approximately 50% of patients by day 7 after intra-arterial thrombolysis-mediated recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed the benefit of thrombolysis with prourokinase, 14 recombinant tissue plasminogen activator (tPA), 15 UV laser, 16 and ultrasound. 17 Antisense oligonucleotides (ODNs) bind to a specific mRNA and prevent its translation to knockdown protein product locally in a time-dependent manner.…”
mentioning
confidence: 99%
“…12,13 This model encompasses appropriate physiological monitoring, associated risk factors for stroke (ie, hypertension and aging), and clinically relevant pathophysiology of thrombosis. A recent immense advance in the practice of the photothrombotic stroke method in the rat achieved by Watson et al 14 is the ultraviolet laser-induced reperfusion method. In the present study we discuss the usefulness of laser methods in establishing stroke models in SHR.…”
mentioning
confidence: 99%
“…In fact, a penumbral region that can be salvaged by pharmacologic intervention or by reperfusion after irreversible damage is produced using photothrombosis [Hao et al, 1992]. Reperfusion is an important clinical aspect of neonatal stroke [Jensen et al, 2003] and modifi cations of the photothrombotic stroke model have been developed to produce a nonpermanent, reversible lesion [Watson et al, 2002]. This study revealed that restoration of blood fl ow following permanent cerebral artery occlusion is achieved by using UV laser irradiation following photochemically induced thrombosis.…”
Section: Discussionmentioning
confidence: 99%